Physics of High-Charge Electron Beams in Laser-Plasma Wakefields - J. Götzfried (American Physical Society, 2020)
Laser wakefield acceleration (LWFA) and its particle-driven counterpart, particle or plasma wakefield acceleration (PWFA), are commonly treated as separate, though related, branches of high-gradient plasma-based acceleration. However, novel proposed schemes are increasingly residing at the interface of both concepts where the understanding of their interplay becomes crucial. Here, we present a comprehensive study of this regime, which we may term laser-plasma wakefields. Using datasets of hundreds of shots, we demonstrate the influence of beam loading on the spectral shape of electron bunches. Similar results are obtained using both 100-TW-class and few-cycle lasers, highlighting the scale invariance of the involved physical processes. Furthermore, we probe the interplay of dual electron bunches in the same or in two subsequent plasma periods under the influence of beam loading. We show that, with decreasing laser intensity, beam loading transitions to a beam-dominated regime, where the first bunch acts as the main driver of the wakefield. This transition is evidenced experimentally by a varying acceleration of a low-energy witness beam with respect to the charge of a high-energy drive beam in a spatially separate gas target. Our results also present an important step in the development of LWFA using controlled injection in a shock front. The electron beams in this study reach record performance in terms of laser-to-beam energy transfer efficiency (up to 10%), spectral charge density (regularly exceeding 10  pC MeV^{−1}), and angular charge density (beyond 300  pC μsr^{-1} at 220 MeV). We provide an experimental scaling for the accelerated charge per terawatt (TW) of laser power, which approaches 2 nC at 300 TW. With the expanding availability of petawatt-class (PW) lasers, these beam parameters will become widely accessible. Thus, the physics of laser-plasma wakefields is expected to become increasingly relevant, as it provides new paths toward low-emittance beam generation for future plasma-based colliders or light sources.